2011
DOI: 10.1111/j.1365-2133.2011.10538.x
|View full text |Cite
|
Sign up to set email alerts
|

Absence of clinical and dermoscopic differences between congenital and noncongenital melanocytic naevi in a cohort of 2-year-old children

Abstract: The number of naevi present in the first 2 years of life is small, and over half have already appeared at birth. They are distributed widely over the skin. BPN are larger than FLN, but most naevi are small. There was no significant difference in the dermoscopic features between the 133 BPN and FLN. The predominant patterns were globular and reticular. We could not identify defined criteria that allowed us to diagnose CMN with certainty and distinguish them from TCN and AMN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
17
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 17 publications
3
17
1
Order By: Relevance
“…Dermoscopic features that we detected with an increased frequency were haloed and target globules, blotches and perifollicular hypopigmentation, compatible with other studies . Hypertrophic hair follicles and extension of naevus cells around follicles may explain the increased frequency of perifollicular hypopigmentation constantly observed in all studies . Focal hypopigmentation was not specifically thought in our study but it was observed, particularly over small hypopigmented nodules, corresponding to neurotization of dermal melanocytes.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Dermoscopic features that we detected with an increased frequency were haloed and target globules, blotches and perifollicular hypopigmentation, compatible with other studies . Hypertrophic hair follicles and extension of naevus cells around follicles may explain the increased frequency of perifollicular hypopigmentation constantly observed in all studies . Focal hypopigmentation was not specifically thought in our study but it was observed, particularly over small hypopigmented nodules, corresponding to neurotization of dermal melanocytes.…”
Section: Discussionsupporting
confidence: 90%
“…No clinical or dermoscopic differences were found between CN and CNLN in our study, and this has been confirmed in a previous study, apart from the increased size and the higher likelihood of irregular borders of CN . The absence of any significant differences supports the congenital nature of CNLN.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations